Role of the federal supreme court in Iraq in strengthening the principle of separation of powers - عبدالله شهاب احمد (Journal of Legal Sciences, 2019)
The constitutional judiciary has played an important role in promoting the separation of authorities in modern regimes. Their constitutions stipulated that there should be a separation of authorities so that each authority can exercise its functions in a manner that does not contradict the work of other authorities. Constitutional justice through the decisions issued by the constitutional judiciary through which the limits of its work is established and the introduction of the principle of separation of authorities from the elements of the legal state and also leads to the protection of the rights of individuals from any abuse may be issued by any authority. And at the same time contributes to the process of the transfer of authorities in a peaceful manner, leading to stability of the state and the stability of the legal situation, so it must be an independent authority to consider disputes between the authorities of the state and find solutions within the framework of the legitimate constitution, The Federal Supreme Court was the supreme authority in resolving disputes between the legislative and executive branches especially when it exceeds one authority over another, and this is what we will review in our research.